1998
DOI: 10.2134/agronj1998.00021962009000010015x
|View full text |Cite
|
Sign up to set email alerts
|

Forage and Nitrogen Yield of Barley—Pea and Oat—Pea Intercrops

Abstract: Barley (Hordeum vulgare L.) and oat (Avena sativa L.) have been intercropped with field pea [Pisum sativum subsp. sativum var. arvense (L.) Poir.] to increase forage yield and quality. Our objective was to evaluate the effects of two barley and two oat cultivars and seeding rates of cereal—pea intercrop on forage production, crude protein (CP) concentration, and N yield. A field experiment was conducted in 1993 and 1994 under dryland management in both fallowed and continuously cropped, no‐tillage environments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
89
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(103 citation statements)
references
References 5 publications
11
89
0
3
Order By: Relevance
“…However, Carr et al (1998) have shown that the forage yields of barley/peas or oats/peas intercrops were higher when the varieties of cereals used had been selected in multi-species stands rather than in intraspecific mixtures using varieties arising from selection in sole crop stands. Thus, the identification of the species and varietal traits suited to intercropping and more generally for low-input systems and organic farming is therefore an important issue and will necessitate reviewing the varietal selection criteria: those used for sole crops are probably not ideal for intercrops and especially for organic farming systems.…”
Section: General Principlesmentioning
confidence: 99%
“…However, Carr et al (1998) have shown that the forage yields of barley/peas or oats/peas intercrops were higher when the varieties of cereals used had been selected in multi-species stands rather than in intraspecific mixtures using varieties arising from selection in sole crop stands. Thus, the identification of the species and varietal traits suited to intercropping and more generally for low-input systems and organic farming is therefore an important issue and will necessitate reviewing the varietal selection criteria: those used for sole crops are probably not ideal for intercrops and especially for organic farming systems.…”
Section: General Principlesmentioning
confidence: 99%
“…Mixtures of annual cereals and legumes can produce large amounts of high-quality forage biomass (Carr et al 1998(Carr et al , 2004Strydhorst et al 2008).…”
Section: Cover Cropsmentioning
confidence: 99%
“…Cover crop mixtures have been observed to be more productive than individual cover crop species grown alone (Wortman et al 2012). Annual forages that are grazed or harvested as hay or silage can be grown as mixtures very successfully, while improving forage quality and productivity (Carr et al 1998). …”
Section: Annual Polyculturementioning
confidence: 99%
“…component contained 29.7% of the variance and explained the positive relationship with each other and with the component of net energy of lactation stem (ENLT), leaf (ENLH) and pin (ENLE) with crude protein pin (PCE) and stems (PCT), neutral detergent fiber shank (FDNE) and dry matter production of the sheet (PSHOJA), while the phenological stage (ETAPA), plant height (ALTURA), production Total dry matter (PSTON), dry matter production of stems and spikes (PSTALLO and PSESPIGA) fibers (FDAH, FDNT, FDNH) and land cover (COB) showed a positive association with each other but negative with the component; whereby said first component can be interpreted in terms of the change that occurs to advance phenological stage, reflecting higher production of dry matter but fodder become more fibrous and woody, reducing protein and energy content, as shown in Figure 1; and this component separates the fibrous and woody those higher protein content and high energy genotypes, higher production. This has been well established and documented for most fodder obtained with small grains (Stark and Wilkinson, 1992;Mc Cartney and Vaage, 1994;Royo et al, 1998;Carr et al, 1998), although overall, without explaining what happens in fractions that compose it.…”
Section: Resultsmentioning
confidence: 69%
“…El primer componente contuvo el 29.7% de la varianza y explicó la relación positiva entre sí y con el componente de las energías netas de lactancia del tallo (ENLT), de la hoja (ENLH) y espiga (ENLE) con la proteína cruda de la espiga (PCE) y tallos (PCT), fibra detergente neutro de la espiga (FDNE) y la producción de materia seca de la hoja (PSHOJA), mientras que la etapa fenológica (ETAPA), altura de planta (ALTURA), producción de materia seca total (PSTON), producción de materia seca de tallos y espigas (PSTALLO y PSESPIGA) fibras (FDAH, FDNT, FDNH) y la cobertura del terreno (COB) mostraron una asociación positiva entre sí pero negativa con el componente; por lo cual dicho primer componente se puede interpretar en términos del cambio que ocurre al avanzar en etapa fenológica, reflejándose en mayor producción de materia seca pero los forrajes se tornan más fibrosos y lignificados, reduciendo su contenido proteico y energético, como se aprecia en la Figura 1; así éste componente separa los genotipos altos, de mayor producción, más fibrosos y lignificados de aquellos de mayor contenido de proteína y energía. Esto ha sido establecido y bien documentado para la mayoría de los forrajes obtenidos con cereales de grano pequeño (Stark y Wilkinson, 1992;Mc Cartney and Vaage, 1994;Royo et al, 1998;Carr et al, 1998), aunque de manera global, sin explicar que sucede en las fracciones que lo componen. component contained 29.7% of the variance and explained the positive relationship with each other and with the component of net energy of lactation stem (ENLT), leaf (ENLH) and pin (ENLE) with crude protein pin (PCE) and stems (PCT), neutral detergent fiber shank (FDNE) and dry matter production of the sheet (PSHOJA), while the phenological stage (ETAPA), plant height (ALTURA), production Total dry matter (PSTON), dry matter production of stems and spikes (PSTALLO and PSESPIGA) fibers (FDAH, FDNT, FDNH) and land cover (COB) showed a positive association with each other but negative with the component; whereby said first component can be interpreted in terms of the change that occurs to advance phenological stage, reflecting higher production of dry matter but fodder become more fibrous and woody, reducing protein and energy content, as shown in Figure 1; and this component separates the fibrous and woody those higher protein content and high energy genotypes, higher production.…”
Section: Resultsunclassified